IAP triple-beam facility for simulation studies of radiation damage of materials - Baturin, V.A.; Yeryomin, S.A.; Litvinov, P.A.; Pustovoitov, S.A.; Roenko, O.Yu.; Storizhko, V.E. (Вопросы атомной науки и техники, 2022)
The project of ion irradiation facility for in-situ studies of radiation damage being developed in IAP NAS of Ukraine is presented. The platform comprises 300 kV heavy ion implanter, 50 kV collinear dual-beam light ion im-planter and 200 kV electron microscope. The optimal energies of heavy and light ion beams have been estimated. The results of computer simulation of ion transmission in the light ion implanter are presented.